Fiber Optics : From Fundamentals to Industrial Applications - Steglich, Patrick; De Matteis, Fabio; Steglich, Patrick; De Matteis, Fabio (IntechOpen, 2019)
Optical fibers in metrology, telecommunications, sensors, manufacturing, and health science have gained massive research interest. The number of applications is increasing at a fast pace. This book aims to present a collection of recent advances in fiber optics, addressing both fundamental and industrial applications. It covers the current progress and latest breakthroughs in emergent applications of fiber optics. The book includes five chapters on recent developments in optical fiber communications and fiber sensors, as well as the design, simulation, and fabrication of novel fiber concepts.
English
Keywords: Other technologies & applied sciences; Applied optics